EFEKTIVITAS PENGGUNAAN KUNYIT (CURCUMA LONGA LINN) TERHADAP DISMENORE PRIMER PADA REMAJA WANITA: TINJAUAN SYSTEMATIC REVIEW - Bella Amelia Putri (2022)
Dysmenorrhea is pain during menstruation in the lower abdomen that radiates to the waist, usually felt on day 2-3 before menstruation and day 1-2 when menstruation occurs, with pain accompanied by heartburn, aches, and stabbing. The high incidence of primary dysmenorrhea sufferers requires the development of an effective management of dysmenorrhea. This study aims to determine the effectiveness of the use of turmeric (C. longa L.) against primary dysmenorrhea in adolescent girls. Several studies on turmeric (C. longa L.) have been conducted, but a more comprehensive description is needed using a systematic review that aims to discuss relevant publications regarding the effectiveness of using turmeric (C. longa L.) against primary dysmenorrhea in adolescent girls. Method: Systematic review with literature search using PubMed, Google Scholar. Literature search using PICO (P: Dysmenorrhea, I: Curcuma longa Linn, C: No comparison, O: Analgesic and Anti-inflammatory and selected using the PRISMA-P method and elimination of journals using the JBI Critical Appraisal Checklist. Results: there are 7 journals with good category which concludes that turmeric (C. longa L.) is an effective analgesic and anti-inflammatory mechanism in reducing primary dysmenorrhea in adolescent girls Conclusion: turmeric (L.) is potentially effective in influencing primary dysmenorrhea in adolescent girls.